The Influence of Pharmacist-Led Initiatives on Hypertension Care - Mathews, Anju Sarah; Kumari, Sreshi (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
Background: In India, the incidence of hypertension is increasing hastily, especially in urban areas. Change in lifestyle and diet along with poor awareness and control is regarded as the main factors influencing the emergence of the condition at a high rate. Objective: The study aimed to analyze the effect of pharmacist interventions in improving blood pressure control. Methods: The prospective interventional study was conducted on a known hypertensive population for more than 2 years. They were randomly categorized into two groups, the interventional group and the usual care group. Pharmaceutical care, involving telephonic follow-up, adherence analysis, and patient education was given in the former group in a time interval of 2 months for about 12 months while the latter was on regular therapeutical care only. In every follow-up period, the pharmacist recorded blood pressure for the usual care group while the interventional group was on constant observation. The difference in blood pressure control was measured in terms of mm/Hg unit. The improvement in the measure from the start and end of the study was analyzed within the group and between the groups. The statistical difference in blood pressure within the group at the start and end of the study and the significance between the two groups was analyzed using SAS Software. Results: The systolic pressures reduced from 141 mmHg to 126 mm Hg in the intervention group and from 142 mm Hg to 134 mm Hg in the usual care group. Similarly, the diastolic pressure decreased from 91 mmHg to 82 mmHg and from 91 mmHg to 86 mmHg in the interventional and usual care group, respectively. Low blood pressure was observed in both groups at the end of the study. However, a statistically significant difference was seen in the interventional group compared to the other. The involvement of pharmacist-led initiatives in hypertensive care helped in the achievement of the AHA (American Heart Association) goal. Conclusions: Including clinical pharmacists in a healthcare team can provide an unerring therapeutic regimen to patients, and lead to overall improvement of patient health.